Pilgrims satisfaction with ambulatory health services in Makkah, 2008 - Ibrahim A Al-Hoqail; Abdelshakour M Abdalla; Abdalla A Saeed; Nasir A Al-Hamdan; Ahmed A Bahnassy (Wolters Kluwer Medknow Publications, 2010)
Objective: The main objective of this study was to assess the level and correlates of patients' satisfaction with ambulatory health services provided for pilgrims during Hajj period in 2008. Materials and Methods: This was a facility-based, cross-sectional study conducted in the Makkah region during the Hajj season in December 2008. A two-stage technique was used to select 500 patients from those who attended the ambulatory health services. One hundred subjects were selected by systematic random sampling (every fifth) from each of the five hospitals included in the study and asked to fill in a pilot-tested self-administered questionnaire. A total of 487 questionnaires were analyzed. Descriptive statistics and t-test, Mann Whitney test and ANOVA, or Kruskal-Wallis test was used as appropriate after checking for normality. Level of significance level was set to be <0.05 throughout the study. Results: From 478 subjects analyzed, 390 (81.6%) were man, 345 (72.2%) were married, 28.9% had either intermediate or high secondary school education, and 2.4% were skilled laborers. The total satisfaction score for health facilities was 20.45 ± 4.03 of 25. The satisfaction scores were 20.15 ± 4.7 of 25 for patient satisfaction with physicians and 21.35 ± 4.5 for patient satisfaction with paramedical personnel. The overall satisfaction score was 61.5 ± 4.5 of 75 points. There were significant relations between total satisfaction of health facilities with education level and with occupation (P = 0.012, 0.001, respectively). The total satisfaction of patients with physicians was significant only with education level. The overall satisfaction score had a significant relation with occupation (P = 0.03), but a borderline relation with the education level (P = 0.056). Conclusion: Satisfaction with ambulatory Hajj health services is acceptable. Some physicians and waiting area services need special attention to improve satisfaction levels with ambulatory health in the subsequent Hajj seasons.